2000
DOI: 10.1103/physreva.63.015602
|View full text |Cite
|
Sign up to set email alerts
|

Exact eigenstates for trapped weakly interacting bosons in two dimensions

Abstract: A system of N two-dimensional weakly interacting bosons in a harmonic trap is considered. When the two-particle potential is a delta function Smith and Wilkin have analytically proved that the elementary symmetric polynomials of particle coordinates measured from the center of mass are exact eigenstates. In this study, we point out that their proof works equally well for an arbitrary two-particle potential which possesses the translational and rotational symmetries. We find that the interaction energy associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition, the large number of compact candidate determinants quickly becomes difficult to handle. As an example, the dimension of the TI-HW eigenspace at (N,M) = (3,9) and L = 8 is only 14, while the number of compact candidates is 1799 (see Table II). We therefore seek to identify a subset of the CF states, to reduce their number without losing the high overlaps with the lower energy exact states.…”
Section: A Full Cf Diagonalizationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the large number of compact candidate determinants quickly becomes difficult to handle. As an example, the dimension of the TI-HW eigenspace at (N,M) = (3,9) and L = 8 is only 14, while the number of compact candidates is 1799 (see Table II). We therefore seek to identify a subset of the CF states, to reduce their number without losing the high overlaps with the lower energy exact states.…”
Section: A Full Cf Diagonalizationmentioning
confidence: 99%
“…The simple states have been found to accomplish just this. 043625-5 In Table II we compare, for different L, the number of candidate determinants for the compact states to the corresponding number of simple state candidates at (N,M) = (3,9). As we see, the latter is significantly lower [29].…”
Section: A Full Cf Diagonalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the formation and properties of vortices in an atomic boson system, the non-vanishing angular momentum states of weakly interacting Bose gase in harmonic trap have attracted considerable attentions [22][23][24][25][26]. In Ref [26], Xia-Ji Liu et al studied the ground state for a weakly interacting, harmonically trapped Nboson system and found that the ground state is generally a fragmented condensate because of the orbital an-gular momentum conservation.…”
Section: Introductionmentioning
confidence: 99%